Mastery of Mathematical Concepts and Problem-Solving Abilities Through Structured Assignment Methods in Junior High School Students - Supardi Uki Sajiman; Hasbullah; Huri Suhendri; Eva Yuni Rahmawati (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2024)
This study aims to describe the influence of the structured assignment method on the mastery of concepts and mathematical problem-solving skills. The method used is an experimental method with the analysis technique used is Manova One Path. The sample in this study is a sample of 72 students at State Junior High Schools in the city of Tangerang. From the results of the analysis, it was obtained: (1) there was an influence of the structured assignment method on the mastery of the concept and the ability to solve mathematical problems in a multivariate manner as evidenced by the value of sig = 0.000 < 0.05 (2) there was an influence of the structured assignment method on the mastery of mathematical concepts univariate as evidenced by the value of sig = 0.006 < 0.05 (3) there was an influence of the structured assignment method on the ability to solve mathematical problems with It is proven that sig = 0.002 < 0.05. To improve the mastery of mathematical concepts and problem-solving skills, teachers should not only use conventional or teacher-centered learning methods but are expected to be able to use learning models that involve students actively learning, including assignment methods that can involve students actively in meaningful learning activities through problem-solving.